PERAN TRANSPORTASI DARAT DALAM MENINGKATKAN PENDAPATAN MASYARAKAT DI KOTA WAISAI KABUPATEN RAJA AMPAT - , Amude K., S.Sos. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Ground tranportation is an attempt move, to transport from one place to another. The object is more useful or can be useful for certain purposes, especially in the city Waisai. During the time, public tranport available are buses, amounting to 4 pieces and two wheelers are more dominant. People who use ground.transportation, thepresenceof a bus is very helpfulfor day activities, but the vehicletaxis are also very helpful, although more costly than the bus fare. This is due to using a motorcycle taxi more quickly arrive at theis destination in the appeal of the vehicles bus only through the route and time. Affect the numbers of users of transport vehicles to the increasing income of the Waisai Town. Purpose of the research is to obtaina decrease or increase in public revenues, who choseto use the bus as an alternative or public transportationvehicles as a means of landtransportation in Waisai Town. Analysis can be concluded, motoristsmay experience an increase in revenuecompared to prior use of ground transportation.